If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4y + -2x + 5y + -5x = 0 Reorder the terms: 6x + -2x + -5x + 4y + 5y = 0 Combine like terms: 6x + -2x = 4x 4x + -5x + 4y + 5y = 0 Combine like terms: 4x + -5x = -1x -1x + 4y + 5y = 0 Combine like terms: 4y + 5y = 9y -1x + 9y = 0 Solving -1x + 9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. -1x + 9y + -9y = 0 + -9y Combine like terms: 9y + -9y = 0 -1x + 0 = 0 + -9y -1x = 0 + -9y Remove the zero: -1x = -9y Divide each side by '-1'. x = 9y Simplifying x = 9y
| 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= | | Sqrt(7x+44)=x | | Ix+7I=2 | | 9-7(5x-8)=63-9x | | 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x | | 8(x-3)=-3x-17 | | -7(3x-5)+8=-21x+43 | | 11x-5-3x+7= | | 41=2x+3x+5 | | 3x+20=5x-24 | | 3+-2t=0 |